Population genetics of caribou in the Alaska-Yukon border region: implications for designation of conservation units and small herd persistence - Mager, Karen Hibbard-Rode (Zenodo, 2024)
Better knowledge of genetic relationships between the Fortymile caribou herd and its neighbors is needed for conservation decision-making in Canada. Here, we contribute the first fine-scale analysis of genetic population structure in nine contiguous caribou herds at the geographic boundaries between Barren-ground and Northern Mountain caribou, and at the Alaska-Yukon border. Using pairwise differentiation metrics, STRUCTURE, and discriminant analysis of principal components (DAPC) to analyze 15 microsatellite loci in 379 caribou, we found complex patterns of genetic differentiation. The Fortymile was the only herd assigned to more than one genetic cluster, indicative of its history as a larger herd whose range expansions and gene flow to other herds were likely important to maintaining diversity across a functioning genetic metapopulation. Some small herds (Chisana, Klaza, and White Mountains) were genetically distinct, while others (Hart River, Clear Creek, Mentasta) exhibited little differentiation from herds they occasionally overlap, including herds assigned to different conservation units (DUs). This genetic connectivity does not result from demographic connectivity, as episodic contact during rut, rather than herd switching, is the likely mechanism. Unusually, one small herd (White Mountains) maintained genetic differentiation despite rut overlap with Fortymile. Our data reveal that some herds with different ecological and behavioral attributes are demographically independent but nonetheless genetically connected. Thus, we suggest that managing caribou for an appropriate level of genetic connectivity, while also supporting herd persistence, will be essential to conserve caribou genetic diversity in the region. Funding provided by: Yukon Department of Environment Crossref Funder Registry ID: https://ror.org/04m0qbj67 Award Number: Funding provided by: Earlham College Crossref Funder Registry ID: https://ror.org/0566sj483 Award Number: Funding provided by: Southern Oregon University Crossref Funder ...